ANALISIS TINGKAT KESADARAN HUKUM TERHADAP KEPEMILIKAN AKTA KELAHIRAN MASYARAKAT DI KELURAHAN SEDANAU KECAMATAN BUNGURAN BARAT KABUPATEN NATUNA - Nurwandi '; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated desire for people who do not have birth certificates that exist in the Village Sedanau. The problem of this research is how the level of legal awareness on birth certificates for people in Sub Sedanau Bunguran District of West Natuna and the factors that cause delays in the administration of birth certificates in the Village Sedanau Bunguran District of West Natuna. The purpose of this study was to determine the level of public awareness in the Village Sedanau Bunguran District of West Natuna and the factors that cause delays in the administration of birth certificates in the Village Sedanau Bunguran District of West Natuna. The study population was as many as 6225 people, and the sample of 70 respondents using purposive sampling technique. Instrument data research is a questionnaire with 20 questions. Analysis of data using qualitative descriptive analysis. Research in the field indicates that respondents who answered